PENGKAYAAN PAKAN BUATAN MELALUI PENAMBAHAN VITAMIN E TERHADAP PERFORMAN EFISIENSI PEMANFAATAN PAKAN, LAJU PERTUMBUHAN RELATIF DAN KELULUSHIDUPAN KEPITING BAKAU (Scylla paramamosain) - Diana Rachmawati; Istiyanto Samidjan (LPPM Universitas Pekalongan, 2014)
Feed is one of the essential biological factors for the growth and survival of mud crab in especially mud crab (S. paramamosain). This study aims to determine the effect of vitamin E on artificial feed for the growth and survival of mud crab (S. paramamosain). This study was conducted from January until March 2014 in the farming village of Tugu Village, Urban Tapak, District Mangkang, Semarang regency for 42 days. Test animals used were of mud crab (S. paramamosain) with an average initial weight 51.04±0.29 g. This study uses the Experimental Method with completely randomized design (CRD) is 4 treatments and 3 replications. The treatments tested were treatment A (artificial feed with vitamin E 0 g/100 g diet), B (artificial feed with vitamin E 0.4 g/100 g feed), C (artificial feed with vitamin E 0.6 g/100 g feed), and D (artificial feed with vitamin E 0.8 g/100 g). Results of this study showed the highest relative growth rate in treatment D (1.33±0.01). Highest utilization efficiency feed achieved by treatment D (27.07±1.22). Value of the survival rate of mud crab (S. paramamosain) ranged from 66.67 until 100.00%. Conclusion in this study is doses of vitamin E on artificial feed significant effect on utilization efficiency feed, relative growth rate but did not significantly effect on survival rate of mud crab (S. paramamosain). The best doses of vitamin E can be added to artificial feed for mud crab (S.paramamosain) was 0.8 g/100 g.